Pig and guinea pig skin as surrogates for human in vitro penetration studies: A quantitative review - Barbero, Ana M.; Frasch, H. Frederick (Toxicology in vitro, 2009)
Both human and animal skin in vitro models are used to predict percutaneous penetration in humans. The objective of this review is a quantitative comparison of permeability and lag time measurements between human and animal skin, including an evaluation of the intra and inter species variability. We limit our focus to domestic pig and rodent guinea pig skin as surrogates for human skin, and consider only studies in which both animal and human penetration of a given chemical were measured jointly in the same lab. When the in vitro permeability of pig and human skin were compared, the Pearson product moment correlation coefficient ( r) was 0.88 ( P < 0.0001), with an intra species average coefficient of variation of skin permeability of 21% for pig and 35% for human, and an inter species average coefficient of variation of 37% for the set of studied compounds ( n = 41). The lag times of pig skin and human skin did not correlate ( r = 0.35, P = 0.26). When the in vitro permeability of guinea pig and human skin were compared, r = 0.96 ( P < 0.0001), with an average intra species coefficient of variation of 19% for guinea pig and 24% for human, and an inter species coefficient of variation of permeability of 41% for the set of studied compounds ( n = 15). Lag times of guinea pig and human skin correlated ( r = 0.90, P < 0.0001, n = 12). When permeability data was not reported a factor of difference (FOD) of animal to human skin was calculated for pig skin ( n = 50) and guinea pig skin ( n = 25). For pig skin, 80% of measurements fell within the range 0.3 < FOD < 3. For guinea pig skin, 65% fell within that range. Both pig and guinea pig are good models for human skin permeability and have less variability than the human skin model. The skin model of choice will depend on the final purpose of the study and the compound under investigation.